Factors Associated With Normal Physiologic Birth for Women Who Labor In Water: A Secondary Analysis of A Prospective Observational Study. (14th January 2022) - Carpenter, Jane; Burns, Ethel; Smith, Lesley
Abstract : Introduction: Research to understand factors associated with normal physiologic birth (unassisted vaginal birth, spontaneous labor onset without epidural analgesia, spinal, or general anesthetic, without episiotomy) is required. Laboring and/or giving birth in water has been shown to be associated with a high proportion of physiologic birth but with little understanding of factors that may influence this outcome. This study explored factors associated with normal physiologic birth for women who labored in water. Methods: We conducted a secondary analysis of a UK‐based prospective observational study of 8064 women at low risk of childbirth complications who labored in water. Consecutive women were recruited from birth settings in England, Scotland, and Northern Ireland. Planned place of birth, maternal characteristics, intrapartum events, and maternal and neonatal outcomes were measured. Univariable and multivariable logistic regression modelling explored factors associated with normal physiologic birth. Results: In total, 5758 (71.4%) of women who labored in water had a normal physiologic birth. Planned birth in the community (adjusted odds ratio [aOR], 2.58; 95% CI, 2.22‐2.99) or at an alongside midwifery unit (aOR, 1.21; 95% CI, 1.04‐1.41) was positively associated with normal physiologic birth compared with planned birth in an obstetric unit. Duration of second stage (aOR, 0.66; 95% CI, 0.62‐0.70), duration in the pool [aOR, 0.93; 95% CI, 0.90‐0.96), and birth weight of the neonate (aOR, 0.74; 95% CI, 0.65‐0.85) were negatively associated with normal physiologic birth. Parity was not associated with normal physiologic birth in multivariate analyses. Discussion: Our findings largely reflected wider research, both in and out of water. We found midwifery‐led birth settings may increase the likelihood of normal physiologic birth among healthy women who labor in water, irrespective of parity. This association supports growing evidence demonstrating the importance of planned place of birth on reducing intervention rates and adds to research on labor and birth in water.